Gibbs equilibrium averages and Bogolyubov measure - Sankovich, D.P. (Вопросы атомной науки и техники, 2012)
Application of the functional integration methods in equilibrium statistical mechanics of quantum Bose-systems is considered. We show that Gibbs equilibrium averages of Bose-operators can be represented as path integrals over a special Gauss measure defined in the corresponding space of continuous functions. We consider some problems related to integration with respect to this measure. Рассмотрено применение методов функционального интегрирования в квантовой равновесной статистической механике бозе-систем. Показано, что гиббсовские равновесные средние бозе-операторов могут быть представлены в виде функциональных интегралов по специальной гауссовой мере, определенной в соответствующем пространстве непрерывных функций. Рассмотрены некоторые вопросы, относящиеся к интегрированию по данной мере. Розглянуто застосування методів функціонального інтегрування у квантовій рівноважній статистичній механіці бозе-систем. Показано, що гибсовські рівноважні середні операторів можуть бути представлені у вигляді функціональних інтегралів по спеціальній гаусовій мірі, визначеній у відповідному просторі безперервних функцій. Розглянуті деякі питання, що відносяться до інтегрування по даній мірі.